Exploring interdepencies and common goals in disaster recovery coordination. (2018) - Raju, Emmanuel; Becker, Per; Tehler, Henrik
Abstract: The present paper seeks to investigate the extent and nature of organizational interdependencies in recovery operations. It focuses on the recovery following the Boxing day tsunami in 2004 in Tamil Nadu, India. It uses the theoretical framework from infrastructure interdependencies to a disaster recovery setting. It takes a case study approach and is based on eighteen interviews conducted in Tamil Nadu. The main findings of this study highlight that there are different types of dependencies between stakeholders. Further, the strength of these dependencies varies between two or more stakeholders. Also, the study indicates that lack of effort in articulating common goals for disaster recovery.